Effect of the incorporation of zinc oxide nanoparticles on the flexural strength of auto- polymerized acrylic resins - Firas Abd Kati (Universidad de Concepción., 2019)
Background: Auto-polymerized acrylic resins are commonly used in many applications in dentistry including in maxillofacial rehabilitation such as interim prostheses, denture repair, reline, orthodontic appliances, record base, among others. These substances, however, have some negative aspects such as poor mechanical properties. Aim: The objective of the current study was to evaluate the effect of incorporating zinc oxide nanoparticles to auto-polymerized acrylic resins on their flexural strength. Materials and methods: Thirty specimens were made from auto-polymerized acrylic resins, divided into three main groups (1 control and 2 experimental). Each group had ten specimens. The two experimental groups comprised the zinc oxide powder at 1% and 2% concentrations, respectively. Acrylic specimens were fabricated with the dimension of 65mm length, 10mm width and 2.5mm thickness according to ISO 1567 specification 1999. Each specimen was subjected to the flexural strength test by a universal testing machine. The crosshead speed for the flexural strength test was 5mm/min until fracture occurred. The SPSS version 16 was utilized for the statistical analysis. The ANOVA and Tukey were used for the comparison among all groups. Results: there was a significant increase (p<0.001) in the flexural strength of the acrylic resins following the addition of zinc oxide particles (control group: 133.27 SD 1.73, ZnO 1%: 154.28 SD 2.90, ZnO 2%: 176.45 SD 0.94). Conclusions: The incorporation of zinc oxide nanoparticles has a significant effect on the flexural strength of auto-polymerized acrylic resins.